Przedsiębiorczość na terenach pogranicza polsko-niemieckiego - Mickiewicz, Antoni; Mickiewicz, Bartosz (Enterprise on Polish-German Borderland, 2006)
The aim of the paper is presentation of enterprise development on Polish-German borderland. The state, possibilities and problems of enterprise development together with euroregional cooperation of German and Polish parishes are also described in the paper.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 106-110